EVIDENCE-BASED POLICY BASED EDUCATION FINANCING REFORM: AN INTEGRATIVE MODEL FOR REALIZING A SUSTAINABLE EDUCATION SYSTEM IN BALIKPAPAN CITY BY 2025 - Hafid Murgantara; Kasmal; Sulfi Ardiansyah; Mukhamad Nurhadi (RADJA PUBLIKA, 2026)
Education financing is a strategic pillar in realizing an inclusive, equitable, and sustainable regional education system. Balikpapan City, which now plays a vital role as the main buffer zone for the Indonesian Capital City (IKN), faces new challenges in the form of a surge in population migration that has triggered a capacity crisis for educational facilities. This study presents an in-depth analysis of education financing policies in Balikpapan City in 2025. Using a qualitative approach with a policy evaluation framework and a literature review, this report evaluates the effectiveness of flagship regional programs such as the Provision of Free Uniforms and Private School Tuition Subsidies funded by the Regional Budget (APBD). Although these programs have successfully alleviated the burden on the community, evidence-based analysis (EBP) found that inefficient poverty data and universal budget allocations make these interventions less effective in addressing the fundamental problem, namely the lack of physical classrooms. As a solution, an Integrative Model for Education Financing was formulated that shifts the funding paradigm towards a Public-Private-People Partnership (PPPP) scheme. This model synergizes the regional budget (APBD) with the optimization of the Balikpapan Mayoral Regulation on One Integrated Regional Data, and draws on Corporate Social Responsibility (CSR) funds from the local oil and gas processing industry. This analysis recommends that the Balikpapan City Government strengthen data digitization to ensure precise subsidy interventions and direct private partnership funds toward school infrastructure development, supporting the vision of Balikpapan Comfortable for All 2045.